Mediators of Atherosclerosis in South Asians Living in America (MASALA) Study: Objectives, Methods, and Cohort Description - Kanaya, Alka M. (Wiley Periodicals, Inc., 2013)
BACKGROUND: South Asians (individuals from India, Pakistan, Bangladesh, Nepal, and Sri Lanka) have high rates of cardiovascular disease (CVD) that cannot be explained by traditional risk factors. There are few prospective cohort studies investigating antecedents of CVD in South Asians. OBJECTIVES: The Mediators of Atherosclerosis in South Asians Living in America (MASALA) study is investigating the prevalence, correlates, and outcomes associated with subclinical CVD in a population‐based sample of South Asian men and women age 40–79 years at 2 US clinical field centers. POPULATION AND METHODOLOGY: This cohort is similar in methods and measures to the Multi‐Ethnic Study of Atherosclerosis (MESA) to allow for efficient cross‐ethnic comparisons. Measurements obtained at the baseline examination include sociodemographic information, lifestyle and psychosocial factors, standard CVD risk factors, oral glucose tolerance testing, electrocardiography, assessment of microalbuminuria, ankle and brachial blood pressures, carotid intima‐media wall thickness using ultrasonography, coronary artery calcium measurement, and abdominal visceral fat measurement using computed tomography. Blood samples will be assayed for biochemical risk factors. Between October 2010 and March 2013, we enrolled 906 South Asians with mean age of 55 ± 9 years (46% women; 98% immigrants who have lived 27 ± 11 years in the United States). The sociodemographic characteristics of this cohort are representative of US South Asians. Participants are being followed with annual telephone calls for identification of CVD events including acute myocardial infarction and other coronary heart disease, stroke, peripheral vascular disease, congestive heart failure, therapeutic interventions for CVD, and mortality. CONCLUSIONS: The MASALA study will provide novel data on the prevalence and associations of cardiovascular risk factors and subclinical atherosclerosis in South Asians living in the United States.